2019
DOI: 10.1075/ip.00024.asp
|View full text |Cite
|
Sign up to set email alerts
|

The pragmatic use of vocatives in private one-to-one digital communication

Abstract: This article examines a corpus of private text messages collected in Birmingham and surrounding towns in 2015. We look specifically at pragmatic roles played by the vocatives we find in the corpus. Since text messages are sent to targeted recipients, vocatives are structurally redundant, and we review literature concerning vocatives in spoken and written data to first see what categories others have proposed for these functions. We then challenge some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…They can be used in the middle of an interactional span, for instance, when a parallel line of talk is introduced by an action label ); alternatively, they may be non-initial. In their study on vocatives in text-messages, Asprey and Tagg (2019) observed that besides initiating interaction via "focusing", terms of address can be recruited to implement relational work of various kinds.…”
Section: Unframed and Framed Dialogue Openings On Whatsappmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used in the middle of an interactional span, for instance, when a parallel line of talk is introduced by an action label ); alternatively, they may be non-initial. In their study on vocatives in text-messages, Asprey and Tagg (2019) observed that besides initiating interaction via "focusing", terms of address can be recruited to implement relational work of various kinds.…”
Section: Unframed and Framed Dialogue Openings On Whatsappmentioning
confidence: 99%
“…When a greeting and an address term are both used, the latter usually comes second. Evidently, when placed after a greeting, an address term does not serve as a "focaliser" (Asprey & Tagg 2019) but is mobilised for other tasks, such as addressing specific recipients in group chats and/or soliciting engagement (cf. Clayman 2013: 292).…”
Section: Greeting-initiated Openings On Whatsapp: a Structural Analysismentioning
confidence: 99%
“…The speaker who is aware of the potential face-threatening effects of the utterance on the addressee attempts to tone down the threat by employing an address term. In the literature, several studies have revealed address terms function as a mitigation device in face-threats, non-conforming utterances, and disagreements (McCarty & O'Keeffe, 2003;O'Keeffe, 2006;Clayman, 2010;Clayman, 2013;Tsakona & Sifianou, 2019;Asprey & Tagg, 2019). Clayman also posits that speakers tend to start the utterance with an address term before they express their disagreement with the hearer, or they want to deny something demanded by the hearer (2010, p.161).…”
Section: Analysis Of the Functionsmentioning
confidence: 99%